Self Theorist: Pengaruh Teori Diri terhadap Motivasi, Kepribadian, dan Pengembangan Diri - Wardani, Silvia; Asbari, Masduki; Misri, Miftahul Jannah (AGUSPATI RESEARCH INSTITUTA, 2024)
This article is a review which is a critical reading of a guidebook that inspires and provides motivation, personality and self-development for its readers, in a book entitled